Pengajian Kitab Akhlak Lil Banin Juz Pertama bagi Remaja Masjid Al-Mukhlisin Desa Air Bagi Kecamatan Concong - Abd. Syahid; Syamsiah Nur; Masriani Masriani; Hasnawati Hasnawati (STAI Auliaurrasyidin Tembilahan, 2021)
The author of the Book of Al-Akhlak Lil Banin is Al-Ustadz 'Umar bin Achmad Baradja, he is a scholar who has very noble character. Since childhood he was raised and educated by his maternal grandfather, Shaykh Hasan bin Muhammad Baradja, a scholar of nahwu and fiqh. Nasab Baradja comes from Seiwun, Hadramaut, Yemen. The spirit of struggle carried out by Al-Ustadz 'Umar bin Achmad Baradja to spread religion and form good moral character in early childhood in Indonesia in general and in Ampel in particular, who saw the moral damage that had undermined the morals of teenagers at that time. So that Al-Ustadz 'Umar Baradja composed as well as compiled the book Al-Akhlak Lil Banin to guide them to always do positive things, such as keeping their bodies clean, clothes, to morals to Allah SWT, parents, teachers, friends and so on. , and the character most described by him is the character of social care. The problems that will be discussed are, (1) Who is Al-Ustadz 'Umar Baradja and his activities (2) What is the thought of Al-Ustadz 'Umar Baradja in the book Al-Akhlak Lil Banin . The thoughts of Al-Ustadz 'Umar Baradja in the book Al-Akhlak Lil Banin are more focused on special morals for boys, because they are prepared for the future to become leaders. If he grows up in noble character and grows up with the right education, he will also become a role model and be obeyed by his children in particular and the wider community in general